2016
DOI: 10.1007/s10815-016-0833-y
|View full text |Cite
|
Sign up to set email alerts
|

First successful trial of preimplantation genetic diagnosis for pantothenate kinase-associated neurodegeneration

Abstract: Purpose We aim to present a case of a healthy infant born after intracytoplasmic sperm injection-in vitro fertilization (ICSI-IVF) with a preimplantation genetic diagnosis (PGD) for pantothenate kinase-associated neurodegeneration (PKAN) due to PANK2 mutation. Methods ICSI-IVF was performed on a Thai couple, 34-yearold female and 33-year-old male, with a family history of PKAN in their first child. Following fertilization, each of the embryos were biopsied in the cleavage stage and subsequently processed for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Currently, the European Society of Human Reproduction and Technology (ESHRE) recommends performing both direct and indirect mutation testing using short tandem repeat (STR) linkage analysis in PGT-M to achieve the highest accuracy rate [24, 25]. Recently, our center has demonstrated successful PGT-M for childhood neurodegenerative disease in cleavage-stage embryos using the power of linkage analysis and SNaPSHOT mini-sequencing for direct mutation detection [26].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the European Society of Human Reproduction and Technology (ESHRE) recommends performing both direct and indirect mutation testing using short tandem repeat (STR) linkage analysis in PGT-M to achieve the highest accuracy rate [24, 25]. Recently, our center has demonstrated successful PGT-M for childhood neurodegenerative disease in cleavage-stage embryos using the power of linkage analysis and SNaPSHOT mini-sequencing for direct mutation detection [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the PANK2 mutation has been identified in all patients with classic PKAN, as demonstrated in our study, the mutation can be identified in only one-third of atypical PKAN patients [10]. Nevertheless, when PKAN is suspected, genetic testing is recommended to confirm the diagnosis in affected patients and presymptomatic diagnosis in other family members.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, homozygosity of this mutation resulted in classic PKAN as demonstrated in our first patient. The c.1103A>G is a novel missense mutation and has never been reported in previous studies [4,[6][7][8][9][10]. Polyphen-2 and Mutation taster softwares predicted the pathogenicity of this mutation to be possibly damaging and disease-causing, respectively, whereas, SIFT predicted the pathogenicity to be tolerated.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation